Role of Beta Bank Sampah Community in Plastic Waste Management in Hative Besar Village, Ambon City - Kappy, Tresia M; Maimina, Steiven; Latue, Philia Christi; Rakuasa, Heinrich (Journal of Community Service and Society Empowerment, 2023)
As an alternative solution to the waste problem, the development of waste banks is one of the social engineering activities that teach people to sort waste and foster public awareness in waste management. The purpose of this study was to determine the role of Beta Waste Bank in managing plastic waste in Hative Besar Village, Teluk Ambon District, Ambon City. The type of research used in this research is descriptive qualitative. This research was conducted in Hative Besar Village, Teluk Ambon District, Ambon City. The subjects in this study were the founders of Beta Bank Sampah and Beta Bank Sampah customers totaling 12 people. The variable in this study uses a single variable, namely the waste bank manager. The single variable will be described by referring to Permen LH No. 13 of 2012. In this study, researchers used several data collection techniques, namely, observation, interviews, questionnaires and documentation. Based on the results of the research conducted, Beta Bank Sampah is a community that is actively engaged in efforts to maintain environmental balance by carrying out the process of recycling plastic waste into economically valuable creations. good awareness efforts towards environmental cleanliness, especially towards the impact of the threat of plastic waste which is increasing along with the growth rate of society. and Beta Bank Sampah has helped the city government in realizing the clean Ambon program by reducing the use of plastic waste in people's lives.